Hubungan Pengetahuan dan Sikap Ibu Tentang Makanan Balita Terhadap Status Gizi Balita Di Desa Malangjiwan, Kecamatan Colomadu, Kabupaten Karanganyar - Lestari, Puput, Dwi Sarbini, SST, M.Kes, Luluk Ria Rakhma, S.Gz., M.Gizi (2015)
Introduction: Nutritional status is health generated between the nutrient needs and input. Food has a very crucial role in growth and development of toddlers. Manultrition can cause disruption of growth in toddlers. Knowledge and attitude of mother are the indirect factors that affect nutritional status of children. Objective: The study aimed to asses the relationship between knowledge and attitude of mother about food for toddlers and the nutritional status of toddlers. Method: The research design was an observasional study with cross-sectional. Subjects w were 33 mothers that had toddlers aged 1-5 years. Retrieval of data used sequential sampling. Knowledge and attitude of mothersdata were obtained by filling out a questionnaire and nutritional status of toddlers obtained by measuring their anthropometry. Result: Most mothers had good knowledge (97,7%) and attitude (100%). Nutritional status of toddlers by BMI/age was good (100%). Correlation test showed p value=0,351 for relationship between knowledge of mothers and nutritional status. The correlation between attitude of mothers and nutritional status showed p value=0,104. Conclusion: There was no correlations between knowledge and attitude of mothers about food for toddlers, and the nutritional status of toddlers at Malangjiwan village, Colomadu, Karanganyar.